2021
DOI: 10.1051/e3sconf/202127312025
|View full text |Cite
|
Sign up to set email alerts
|

Technologies of active learning in the context of the risks of modern professional education

Abstract: The article includes a comprehensive analysis of the specifics of the system of active learning methods and a description of its resources in the professional training of future specialists in the context of modern modernization of higher education. Based on the results of the analysis of current trends in the development of a variety of technologies and formats of training in higher education, the criteria for determining their feasibility are identified. The paper presents an overview of the significant psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The findings of this study are supported by the results of previous studies involving 219 students in grades 8-9 where the results show that the use of digital technology in learning contributes to the improvement of independent learning skills [10]. Meanwhile, the results of other studies [3] show that the active learning method is not effective enough in developing independent learning skills. Therefore, there needs to be synergy between the use of learning methods and strategies as well as technology-based learning media in developing independent learning skills.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings of this study are supported by the results of previous studies involving 219 students in grades 8-9 where the results show that the use of digital technology in learning contributes to the improvement of independent learning skills [10]. Meanwhile, the results of other studies [3] show that the active learning method is not effective enough in developing independent learning skills. Therefore, there needs to be synergy between the use of learning methods and strategies as well as technology-based learning media in developing independent learning skills.…”
Section: Discussionsupporting
confidence: 82%
“…independent learning skills develop from the application of distance learning or online learning which has elements of learning videos, independent assignments, and evaluations aimed at assessing students' own knowledge [2]. The development of independent learning skills can occur through active and innovative learning methods such as research activities carried out by students [3]. In addition, technological developments that provide the latest information also play an important role in developing independent skills [2].…”
mentioning
confidence: 99%
“…A study involving 219 students in grades 8-9 demonstrated that the use of digital technologies contributes to the boost of self-esteem and improvement of self-learning skills (Efremova et al, 2020). According to scientists (Scherbakova et al, 2021), students themselves believe that active learning methods are not highly effective in developing self-educational skills. Creative approach influences the teachers' professional development.…”
Section: Discussionmentioning
confidence: 99%
“…(Matviishyn & Luhova, 2021). The skills that future specialists need for self-education are developed in higher educational institutions through teaching methods that involve independent active work of students case methods (Yaremych, 2021), project method, brainstorming (Scherbakova et al, 2021), use of media resources (Umarova, 2020; Zakhro, 2020), educational platforms (Kuwana et al, 2018), building the block-modular learning process (Toirova et al, 2020), comprehensive use of ICT (Kapucu & Turk, 2020), as well as independent work that is part of the curriculum (Yaremych, 2021). The development of self-learning skills is also promoted by electronic courses developed by teachers, which include texts and videos of lectures, assignments for self-control and self-completion, tests and electronic methods of assessing the level of students' knowledge (Umarova, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation